Penerapan Model Pembelajaran Berbasis Proyek Pada Mata Pelajaran Seni Budaya Untuk Meningkatkan Minat Dan Kreativitas Siswa Kelas IVA UPT SPF SD Inpres Tamamaung IV Kota Makassar - Nurmia Nurmia; H. Nurdin; Roslyn Roslyn (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The main problem in this research is in learning activities where based on observations that have been made it was found that problems exist in class IVA, namely that there are still some students who have a lack of interest in learning and their level of creativity is also lacking because the teacher still uses conventional methods. So the author decided to conduct research in this class to make improvements using a project-based learning model. This research aims to determine the application of the project-based learning model to increase the interest and creativity of class IVA UPT SPF SD Inpres Tamamaung IV students, Makassar City. This type of research is Classroom Action Research (PTK) which includes four stages, namely planning, implementation, observation and reflection. The subjects of this research were 22 students in class IVA UPT SPF SD Inpres Tamamaung IV, Makassar City. This research instrument uses teacher activity observation sheets, student interest observation sheets and student creativity observation sheets. Then this data is analyzed using the average formula. From the results of this research, the average results of observation of teacher activities in cycle I were 56% (Poor) with an increase in cycle II of 90% (Very Good). The results of observing student interest in the first cycle were 69% (fairly good) and increased in the second cycle by 89% (very good). Meanwhile, student creativity also increased, in cycle I with a percentage of 74.43% (Medium Creativity) and experienced an increase in cycle II with a percentage of 80.10% (High creativity). Thus, the project-based learning model can increase student interest and creativity in Arts and Culture subjects. with material on Simple Comics and Making Curtains from Used Materials in class IVA UPT SPF SD Inpres Tamamaung IV Makassar City.